Adenosine A2A receptor availability in patients with early- and moderate-stage Parkinson’s disease - Waggan Imran; Rissanen Eero; Tuisku Jouni; Joutsa Juho; Helin Semi; Parkkola Riitta; Rinne Juha O; Airas Laura (SPRINGER HEIDELBERG, 2025)
Introduction Adenosine 2A (A(2A)) receptors co-localize with dopamine D-2 receptors in striatopallidal medium spiny neurons of the indirect pathway. A(2A) receptor activation in the striatum or pallidum decreases D-2 signaling. In contrast, A(2A) receptor antagonism may help potentiate it. Furthermore, previous PET studies have shown increased A(2A) receptor availability in striatum of late-stage PD patients with dyskinesia. However, human in vivo evidence for striatal A(2A) receptor availability in early-stage PD is limited. This study aimed to investigate possible differences in A(2A) receptor availability in the striatum and pallidum of early- and moderate-stage PD patients without dyskinesias. Methods Brain MRI and PET with [C-11]TMSX radioligand, targeting A(2A) receptors, was performed in 9 patients with early- and 9 with moderate-stage PD without dyskinesia and in 6 healthy controls. Distribution volume ratios (DVR) were calculated to assess specific [C-11]TMSX binding in caudate, putamen and pallidum. Results A(2A) receptor availability (DVR) was decreased in the bilateral caudate of early-stage PD patients when compared with healthy controls (P = 0.02). Conversely, DVR was increased bilaterally in the pallidum of moderate-stage PD patients compared to healthy controls (P = 0.03). Increased mean striatal DVR correlated with higher motor symptom severity (rho\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$rho$$\end{document} = 0.47, P = 0.02). Conclusion Our results imply regional and disease stage-dependent changes in A(2A) receptor signaling in PD pathophysiology and in response to dopaminergic medication.